1967
DOI: 10.2307/4593012
|View full text |Cite
|
Sign up to set email alerts
|

Primary Isolation of N. gonorrhoeae with a New Commercial Medium

Abstract: THE DIAGNOSIS of gonorrhea in the fe¬ male is notoriously difficult and fallible. New and reliable diagnostic methods are urgently needed if we are to control the disease.A new commercial culture medium for the primary isolation of Neisseria gonorrhoeae has been developed by the Baltimore Biological Laboratory (BBL). This medium differs from other conventional commercial chocolate media in that the added enrichment, instead of being blood or yeast extract, is chemically defined (1).A trial of this medium was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…MH agar supplemented with hemoglobin and IsoVitaleX is used for antibiotic susceptibility testing of Haemophilus influenza (16). A1though IsoVitaleX is an enrichment recommended for isolating Neisseria gonorrhoeae (13), MH agar with the supplement is not noted for growing extremely fastidious bacteria. Growth studies with the LDB revealed that cultural conditions, including pH and incubation temperature, strongly influence the abiity to support growth of the LDB from infected tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MH agar supplemented with hemoglobin and IsoVitaleX is used for antibiotic susceptibility testing of Haemophilus influenza (16). A1though IsoVitaleX is an enrichment recommended for isolating Neisseria gonorrhoeae (13), MH agar with the supplement is not noted for growing extremely fastidious bacteria. Growth studies with the LDB revealed that cultural conditions, including pH and incubation temperature, strongly influence the abiity to support growth of the LDB from infected tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The term Legionnaires disease was first used in the summer of July 1976 to describe an outbreak of acute respiratory illness that occurred in Pennsylvania, predominantly among members of the American Legion attending a statewide convention in Philadelphia. A gram-negative pleomorphic bacterium was ultimately shown to be the etiological agent of the epidemic in Philadelphia (5,7,13), as well as of four previously unsolved or undetected outbreaks (1-3). This paper described (i) the bacteriological methods first used to grow the Legionnaires disease bacterium (LDB) on artificial medium by one of the authors (R.E.W.…”
mentioning
confidence: 99%
“…Although N. gonorrhoeae has been clinically recognized for centuries, N. gonorrhoeae culture, particularly from microbiologically complex sites such as the female genital tract, the rectum, and the pharynx, was challenging due to frequent bacterial overgrowth. In about 1967, development and introduction of selective gonorrhea culture media permitted improved diagnosis, particularly for women, in whom culture yield was increased over 50% (41, 42). These media provided an important tool to better define the high prevalence of gonorrhea and laid the groundwork for increased U.S. Public Health Service (USPHS) emphasis on gonorrhea control.…”
Section: Gonorrhea Diagnosismentioning
confidence: 99%
“…In the 1960’s, the Venereal Disease Research Laboratory (VDRL) of the USPHS expanded its focus to more fully consider gonorrhea as a public health threat. These changes were facilitated by appreciation of rapidly increasing infection rates (4) resulting in part from increasing use of recently developed selective culture media, (41, 42) In 1964, CDC authors reported that failure rates in women treated for uncomplicated gonorrhea ranged from 20–40% for 10 regimens which included 1.2 million units of procaine or benzathine penicillin G, 3.0 grams of tetracycline, and single doses of streptomycin (1.0g), chloramphenicol (1.0g), or six 500 mg doses of tetracycline (49). In 1970, the CDC also published results of 14-year study of gonococcal susceptibility to penicillin, confirming that increasing penicillin MICs were associated with increased likelihood of treatment failure (11).…”
Section: Role Of the Us Public Health Service (Usphs) And Centers Fmentioning
confidence: 99%